Cost-benefit analysis of bank regulation: Does size matter? - Hillary Mulindi (Kenya Bankers Association (KBA), 2021)
This study investigates the trade-off between costs and benefits of bank regulation in Kenya. Using the Stochastic Frontier Analysis (SFA) and Annual data for the period 2003 - 2019, extracted from KBA Financial Database and KNBS macroeconomic data, the study models Industry-level and cluster level relationship between bank regulation and cost inefficiency of banks. The industry-level analysis indicates that stringent capital requirement has a positive and significant effect on the cost-efficiency of banks, while tighter liquidity requirements hurt cost efficiency. Further, the bank tier-level analysis established that the double-layered regulatory framework creates Cost inefficiencies amongst middle-tier banks. The key policy implication would be to consider reviewing, identifying, and amending the regulatory provisions that are creating inefficiencies among the listed middle-tier banks
Keywords: G28; D61; C24; 330; Bank Regulation; Cost-Benefit Analysis; Stochastic Frontier Analysis